2007
DOI: 10.1186/1477-7827-5-20
|View full text |Cite
|
Sign up to set email alerts
|

Testicular involution prior to sex change in gilthead seabream is characterized by a decrease in DMRT1 gene expression and by massive leukocyte infiltration

Abstract: Background: Leukocytes are found within the testis of most, if not all, mammals and are involved in immunological surveillance, physiological regulation and tissue remodelling. The testis of seasonal breeding fish undergoes a regression process. In the present study, the second reproductive cycle (RC) of the protandrous seasonal teleost fish, gilthead seabream, was investigated and the presence of leukocytes analysed. Special attention has been paid to the testicular degenerative process which is particularly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
79
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(83 citation statements)
references
References 37 publications
4
79
0
Order By: Relevance
“…In contrast, suppression of DMRT1 transcripts in the gonads was observed in estrogen (E2)-treated male embryos of zebrafish (Schulz et al 2007) and tilapia ). In addition, changes were noticed in DMRT1 expression in concordance with the phases of testicular differentiation in several fishes that change their sexes naturally (Alam et al 2008;He et al 2003;Liarte et al 2007). These findings suggest that DMRT1 is involved not only in early testicular differentiation, but also in gonadal sex reversal/change in teleosts.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, suppression of DMRT1 transcripts in the gonads was observed in estrogen (E2)-treated male embryos of zebrafish (Schulz et al 2007) and tilapia ). In addition, changes were noticed in DMRT1 expression in concordance with the phases of testicular differentiation in several fishes that change their sexes naturally (Alam et al 2008;He et al 2003;Liarte et al 2007). These findings suggest that DMRT1 is involved not only in early testicular differentiation, but also in gonadal sex reversal/change in teleosts.…”
Section: Introductionmentioning
confidence: 99%
“…As a group of protogynous hermaphrodite fishes that the gonad development undergoes transition from ovary to intersexual gonad and then to testis, and cells at different stages during oogenesis and spermatogenesis can be synchronously observed in the transitional gonads, groupers have been used as a good model for mining sex determination or sex differentiation-related genes. Xia et al [75] have found that grouper DMRT1 is specifically expressed in spermatogenic cells during female-to-male sex reversal, and the spermatogenic cell-specific and dynamic expression pattern was revealed to be basically similar in several sex reversal fishes including protogynous wrasse (Halichoeres tenuispinis) [76] and rice field eel (Monopterus albus) [77] as well as protandrous black porgy (Acanthopagrus schlegeli) [78,79] and gilthead seabream (Sparus aurata) [80].…”
Section: Sex Determination and Candidate Sex Determination Genesmentioning
confidence: 99%
“…During post-spawning the proliferative activity was resumed, although necrotic areas and apoptotic germ cells were also observed (Chaves-Pozo et al, 2005a;Liarte et al, 2007). Interestingly, the last stages of each reproductive cycle (resting and testicular involution, respectively) differed completely.…”
Section: Characterization Of Immune Cells and Molecules In The Gonadsmentioning
confidence: 92%
“…Secondly, the infiltration of acidophilic granulocytes depended on the reproductive cycle stage of the specimens and it was strongly regulated by soluble factors produced by the gonad (ChavesPozo et al, 2003(ChavesPozo et al, , 2005a(ChavesPozo et al, , 2005b. Moreover, this migratory influx increased the amount of acidophilic granulocytes in the testis at specific stages (post-spawning and testicular involution) coinciding with a very low proliferative activity of germ cells and with the appearance of necrotic areas and apoptotic germ cells , 2005aLiarte et al, 2007). Interestingly, the ultrastructure of these testicular acidophilic granulocytes at the testicular involution stage strongly suggests their involvement in the renewal process that takes place in the gonad at post-spawning and testicular involution stages .…”
Section: Characterization Of Immune Cells and Molecules In The Gonadsmentioning
confidence: 95%
See 1 more Smart Citation